Extended‐duration thromboprophylaxis for abdominopelvic surgery: Development and evaluation of a risk‐stratified patient decision aid to facilitate shared decision making. Issue 8 (14th November 2022) - Ivankovic, Victoria; McAlpine, Kristen; Delic, Edita; Carrier, Marc; Stacey, Dawn; Auer, Rebecca C.
Abstract: Background: Extended‐duration thromboprophylaxis is used to decrease risk of venous thromboembolism (VTE) after surgery but may increase the risk of bleeding. The decision to complete a course of extended‐duration thromboprophylaxis can be challenging. Objective: The objective of this study was to develop an acceptable patient decision aid (PtDA) to facilitate shared decision making for the use of extended‐duration thromboprophylaxis following major abdominal surgery. Methods: An evidence‐based, risk‐stratified PtDA was created. The evidence on benefits and harms of a 28‐day postoperative course of low‐molecular‐weight heparin (LMWH) versus in‐hospital prophylaxis only were synthesized. Outcomes included minor bleeding, major bleeding, clinically significant VTE, and fatal VTE. Risks were calculated and reported by Caprini score. Alpha testing of the PtDA draft with various stakeholders was performed using a 10‐question survey to assess acceptability of the PtDA with patients, thrombosis experts, and surgeons. The primary outcome was the acceptability of the PtDA. Results: Acceptability testing was performed with 11 patients, 11 thrombosis experts, and 11 surgeons. Most responders felt the language on the PtDA was easy to follow (28/33, 85%), and that the information was well balanced between management options (9/11 [82%] patients; 17/21 [80%] clinicians). Most patients (9/11, 82%) and clinicians (18/22, 82%) believed it would be a useful clinical tool, and were satisfied with the overall quality of the PtDA (27/33, 82%). Conclusions: A risk‐stratified, evidence‐based PtDA was created to facilitate shared decision making for the use of extended‐duration LMWH following major abdominal surgery. This clinical tool was acceptable with patients and physicians and is available at https://decisionaid.ohri.ca/decaids.html .